2021
DOI: 10.3389/fcell.2020.579945
|View full text |Cite
|
Sign up to set email alerts
|

Circ0083429 Regulates Osteoarthritis Progression via the Mir-346/SMAD3 Axis

Abstract: Osteoarthritis (OA) is a degenerative joint disease. Currently, apart from symptomatic treatment or joint replacement, no other effective treatments for OA exist. The mechanisms underlying OA remain elusive and require further research. Circular RNAs (circRNAs) are known to be involved in many diseases; however, their function in OA is not yet fully understood. Here, we identified a novel circRNA, Circ0083429. The role of Circ0083429 in OA was confirmed via western blot (WB), quantitative real-time PCR (qRT-PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 48 publications
1
2
0
Order By: Relevance
“… 45 The interaction between circ0083429 and miR‐346 can regulate osteoarthritis progression. 46 For the first time, the present study reported a decrease in miR‐346 expression in the RVLM of SHRs when compared with healthy controls. The enhancement of miR‐346 expression in RVLM can effectively inhibit neuronal excitability, sympathetic outflow, and lower BP, offering improvements in hypertension symptoms.…”
Section: Discussionsupporting
confidence: 49%
“… 45 The interaction between circ0083429 and miR‐346 can regulate osteoarthritis progression. 46 For the first time, the present study reported a decrease in miR‐346 expression in the RVLM of SHRs when compared with healthy controls. The enhancement of miR‐346 expression in RVLM can effectively inhibit neuronal excitability, sympathetic outflow, and lower BP, offering improvements in hypertension symptoms.…”
Section: Discussionsupporting
confidence: 49%
“…Recently, the regulatory potential of circRNAs in OA has attracted increased attention 35 . For example, studies have shown that circSERPINE2 alleviates chondrocyte apoptosis and promotes anabolism of the ECM through the mir1271-5p/ERG pathway 36 ; the ciRS-7/miR-7 axis ameliorates cartilage degradation and inhibits autophagy via PI3K/AKT/mTOR activation 37 ; circPDE4D regulates glycosaminoglycan composition and inhibits matrix degeneration enzymes 38 ; and circ0083429 regulates the ECM by downregulating miR-346/Smad3 in chondrocytes 39 . According to our previous study, the chondrogenic differentiation of MSCs started 7 days after induction, with cartilage matrix gradually synthesized, reaching the peak of the expression of Collagen II and Aggrecan at days 14–21, while matrix metalloproteinases (MMPs) and indicators of chondrocyte hypertrophy increased rapidly.…”
Section: Discussionmentioning
confidence: 99%
“…CircRNA, circular RNA; FGF, fibroblast growth factor; FUT2, fucosyltransferase 2; GREM, gremlin; miR, microRNA; TRAF2, TNF receptor-associated factor 2 of circ_DHRS3 and circPDE4D may alleviate OA. circ0083429 regulates Smad3 by sponging miRNA-346, thereby alleviating OA through the miR-346/Smad3 axis (52). circCDH13 promotes OA by sponging miR-296-3p, contributing to OA pathogenesis via the circCDH13/miR-296-3p/PTEN axis (53).…”
Section: Circrnas and Oa Treatmentmentioning
confidence: 99%